Analisis Usahatani Pola Tanam Sayuran pada Lahan Gambut - Wawan Eka Putra; Andi Ishak; Rokhani Rokhani (UPT Penerbitan Universitas Jember, 2018)
Cropping pattern is the activity of planting one or several types of plants on the same land in a certain period. The selection of certain cropping patterns is determined by various factors, one of which is the value of farming profits. This study aims to analyze the advantages of vegetable cropping patterns on peat land in the Mutiara Farmer Group, Panca Mukti Village, Pondok Kelapa District, Bengkulu Tengah Regency. There are two cropping patterns of vegetable crops in a year applied by farmers in Mutiara Farmer Group namely cucumber – bitter melon - long beans and cucumber – squash – long beans. Data was collected from August to September 2018 through FGD and field observations. The FGD involved 7 vegetable farmers. Data were analyzed comparatively using the R-C ratio. The results showed that the cucumber – bitter melon – long beans cropping pattern was more profitable with a receipt value of Rp. 54,135,500/hectare/year compared to the cucumber – squash – long beans planting pattern of Rp. 51,830,500/hectare/year. The R/C in the two cropping patterns was 1.28 and 1.27 respectively.